Pengaruh Efektifitas Daun Katuk Terhadap Kecukupan Asi Pada Ibu Menyusui Di Desa Pagintungan - Siti Halimatussa’diyah; Nuryani Nuryani (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background: Production of breast milk is influenced by prolacine hormones and oxytocin. An exclusive provision of breast milk is to improve the growth and development of infants and their health. Research objectives: To find out if there is a influence of the effectiveness of the katuk leaves to the adequacy of breast milk in Pagintungan village. Research method: Used in this study is quantitative research with pre experimental methods with the design of One group Pretest- Posttest Design. Collection of data by sharing an observation sheet of 30 people. Sampling in this study used Purposive Sampling and analysis of bivariate data using Wilcoxon test. The results of the research in the value of P value = (0.00 < 0.05) Then there is expressed influence of water inhalation of the leaf decoction is effective in increasing breast milk in breastfeeding mothers. Conclusion: There is an effective influence on the stew of the leaves of the catuk to the adequacy of breast milk in Pagintungan village.